Carboxyl-Functionalized Carbon Nanotubes Loaded with Cisplatin Promote the Inhibition of PI3K/Akt Pathway and Suppress the Migration of Breast Cancer Cells - Madalina Andreea Badea; Mihaela Balas; Mariana Prodana; Florentina Gina Cojocaru; Daniela Ionita; Anca Dinischiotu (MDPI AG, 2022)
PI3K/Akt signaling is one of the most frequently dysregulated pathways in cancer, including triple-negative breast cancer. With considerable roles in tumor growth and proliferation, this pathway is studied as one of the main targets in controlling the therapies' efficiency. Nowadays, the development of nanoparticle-drug conjugates attracts a great deal of attention due to the advantages they provide in cancer treatment. Hence, the main purpose of this study was to design a nanoconjugate based on single-walled carbon nanotubes functionalized with carboxyl groups (SWCNT-COOH) and cisplatin (CDDP) and to explore the potential of inhibiting the PI3K/Akt signaling pathway. MDA-MB-231 cells were exposed to various doses (0.01-2 µg/mL SWCNT-COOH and 0.00632-1.26 µg/mL CDDP) of SWCNT-COOH-CDDP and free components for 24 and 48 h. In vitro biological tests revealed that SWCNT-COOH-CDDP had a high cytotoxic effect, as shown by a time-dependent decrease in cell viability and the presence of a significant number of dead cells in MDA-MB-231 cultures at higher doses. Moreover, the nanoconjugates induced the downregulation of PI3K/Akt signaling, as revealed by the decreased expression of PI3K and p-Akt in parallel with PTEN activation, the promotion of Akt protein degradation, and inhibition of tumor cell migration.